Accuracy and properties of German business cycle forecasts - Steffen Osterloh (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
In this paper the accuracy of a wide range of German business cycle forecasters is assessed for the past 10 years. For this purpose, a data set is used comprising forecasts published on a monthly basis by Consensus Economics. The application of several descriptive as well as statistical measures reveals that the accuracy of the 2-years forecasts is low relative to a simple na?ve forecast. This observation can mainly be explained by a systematic overestimation of the growth rates by the forecasters. Moreover, the lack of accuracy can also be explained partly by insufficient information efficiency as well as imitation behaviour. Finally, it is shown that notwithstanding the common errors which affected the accuracy of all forecasters mainly because of their systematic overestimation, they differ significantly in their forecast accuracy.
Keywords: E37; E32; C52; 330; business cycle forecasting; forecast evaluation; Consensus forecasts